2010
DOI: 10.1007/s10750-010-0207-x
|View full text |Cite
|
Sign up to set email alerts
|

Movement patterns and habitat use of three declining littoral fish species in a north-temperate mesotrophic lake

Abstract: We explored patterns of habitat use and movement of three declining fish species intolerant to eutrophication in a north-temperate (Minnesota, USA) glacial lake: the blackchin shiner Notropis heterodon, blacknose shiner Notropis heterolepis, and banded killifish Fundulus diaphanus. We marked individuals with elastomer tags and estimated movement distances of recaptured individuals. Estimated home ranges for all species ranged from 3,264 to 19,525 m 2 , which covered 0.8 and 5.0% of our study lake's total litto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Direct comparisons to previous movement studies are difficult due to differing monitoring methods, timing, duration of studies, and limited knowledge of movement patterns of nongame fishes. However, movement was quantified for two species in Fundulidae: blackspotted topminnow, Fundulus olivaceus (Smithson & Johnston 1999) and banded killifish, Fundulus diaphanous (Valley et al 2010). Adult blackspotted topminnow regularly moved among study pools in a dynamic lotic system at rates that exceeded other taxa evaluated (i.e., creek chub, Semotilus atromaculatus, green sunfish, and longear sunfish, Lepomis megalotis), similar to our results for plains topminnow.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Direct comparisons to previous movement studies are difficult due to differing monitoring methods, timing, duration of studies, and limited knowledge of movement patterns of nongame fishes. However, movement was quantified for two species in Fundulidae: blackspotted topminnow, Fundulus olivaceus (Smithson & Johnston 1999) and banded killifish, Fundulus diaphanous (Valley et al 2010). Adult blackspotted topminnow regularly moved among study pools in a dynamic lotic system at rates that exceeded other taxa evaluated (i.e., creek chub, Semotilus atromaculatus, green sunfish, and longear sunfish, Lepomis megalotis), similar to our results for plains topminnow.…”
Section: Discussionsupporting
confidence: 82%
“…The observation of large-scale movement behaviors for both species emphasizes the importance of movement to the life history of this family of fishes (Smithson & Johnston 1999). Banded killifish also exhibited similar movement patterns to plains topminnow and generally moved greater distances than blackchin shiner, Notropis heterodon, and blacknose shiner, Notropis heterolepis, in a lentic system (Valley et al 2010). Despite traveling greater distances (maximum distance: 1813 m) than plains topminnow, banded killifish exhibited a more limited linear home range likely as a result of uniform habitat distribution in the lentic system relative to the longitudinal habitat mosaic common to lotic environments (Valley et al 2010).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Currently researchers have focused on responses of sport fishes to invasive species; therefore, a diversification of research effort to assess impacts on phytophylic fishes (especially rare and threatened species) is necessary to assess what different responses fish species have to invasions. For instance, Valley et al (2010) observed that fishes with declining populations (i.e., killifish, darters, and rare minnows) were positively associated with plant biovolume of a native macroalgae (Chara sp.). In the event of an invasion, Chara would likely be replaced by invasive macrophytes, but fish response to this change would be difficult to predict.…”
Section: Future Research Needsmentioning
confidence: 99%
“…For example, increased water clarity favors turbidity-intolerant species such as blackchin shiner (Notropis heterodon) and blacknose shiner (Notropis heterolepis) (Cvetovik et al, 2010;Minns et al, 1994;Valley et al, 2010). Fish species richness, abundance and biomass are generally found to be higher in the presence of macrophytes (Cvetovik et al, 2010;Pratt and Smokorowski, 2003;Randall et al, 1996); nevertheless certain small fish species favor non-vegetated habitats (e.g.…”
Section: Introductionmentioning
confidence: 99%